Accelerating green finance for a sustainable future - Mukesh Kumar Mishra (ResearchGate, 2024)
India's goal of net-zero emissions by 2070 is a significant step towards addressing climate change. Green financing, a practice directing financial resources from sectors like banking, micro-credit, insurance, and investment towards projects with positive environmental and social impacts, is crucial for achieving this goal. It aligns financial flows with environmental protection, social well-being, and long-term sustainability. SEBI's efforts on green bond principles support environmentally friendly projects, mitigating climate change, and promoting social well-being. Collaboration between governments, financial institutions, investors, businesses, and civil society is essential for driving positive change.
Keywords: Q56; Q58; G23; G28; 330; Green Finance; Environmental Economics